PENANAMAN NILAI KARAKTER PEDULI LINGKUNGAN PADA SISWA SD NEGERI PLEBURAN 04 SEMARANG - Jihan Nura Sekar Manik (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This qualitative study aims to find out how to instill the values ​​of environmentally responsible characters and responsibilities in students at Adiwiyata School. This research was conducted at Pleburan 04 Semarang Elementary School which is the PPK and Adiwiyata Schools. Routine activities in the context of forming environmental character in students are carried out through daily, weekly and occasional activities. The activity of forming an environmentally friendly character in students of the adiwiyata elementary school Pleburan 04 Semarang which is done at any time is the habituation of LISA operations (See Trash Take) to maintain school cleanliness. This activity is effective in forming the habit of caring for the environment in all adiwiyata students at SD Negeri Pleburan 04 Semarang because there are no student attitudes that are not in accordance with the direction of the goal of forming the main values ​​of the character, the teacher always conducts ongoing training so that the formation of character values ​​becomes a habit and a living culture adiwiyata school student Pleburan 04 Public Elementary School Semarang.